The Use of Assistive Technology for People with Special Needs in the UAE - Almekhalfi, Abdurrahman Ghaleb; Tibi, Sana (Journal of the American Academy of Special Education Professionals, 2010)
Today, technology has become an essential part of the everyday educational setting. Its use has proven to facilitate learning and communication of many students with and without disabilities. Assuredly, assistive technology (AT) has transformed education and empowered students with disabilities. However, research studies investigating AT for students with special needs in the United Arab Emirates (UAE) are limited, if any. Quantitative and qualitative data collection methodology were used to explore the AT tools, services, barriers, and professional development available in the UAE special needs centers. Results showed that different AT devices existed according to the types of disabilities. In addition, results revealed different types of barriers hindering the use of AT. Results may shed light on the use of AT in the UAE, teachers’ perceptions towards this use and barriers impeding such use. Recommendations and suggestions to improve the use of AT wherever and whenever needed in the UAE are discussed.